Literature Review of the Measurement in the Innovation Management - Melendez, Karin; Dávila, Abraham; Melgar, Andrés (Journal of technology management & innovation, 2019)
Organizations create innovation strategies to improve their productivity and the competitive advantage. In this sense, innovation management facilitates the realization of innovation. It is known that measurement is important in the management processes; however, there is no classification of the contributions in these subjects. Therefore, in this study we identify publications that involve measurement and analysis in the management of innovation. Our study used a systematic mapping of the literature and it shows that in recent years there has been an increase in research on measurement, however, there are few studies and only for certain industrial sectors, sizes of companies and countries. Hence, there is a little worked research space which can be more developed.